When Communication Fails: Understanding Interpersonal Dynamics in the Medkom Division of HIMAKOM UAD - Nur Asfia; Sumarlan, Iman (Forum Akademisi dan Dosen Peneliti (FAST), 2025)
Effective interpersonal communication is essential to the functioning of student-led organizations, which depend on voluntary participation and strong internal cohesion. This study examines how communication failures influence interpersonal dynamics within the Media and Communication Division (Medkom) of HIMAKOM UAD, a unit responsible for managing the organization’s public communication and social media presence. Despite its strategic role, Medkom experienced sustained communication breakdowns that disrupted collaboration and weakened member relationships. Using a descriptive qualitative approach supported by organizational ethnography, the research draws on complete participant observations and in-depth interviews with eight informants, including division members, HRD representatives, and HIMAKOM leadership. Findings show that communication failure in Medkom stemmed from three interrelated factors: the absence of early team bonding and shared expectations, limited leadership involvement in facilitating interaction, and misaligned perceptions of responsibility. These issues generated mistrust, interpersonal tension, and emotional withdrawal, preventing the division from developing effective group processes. As a result, productivity declined, content output became inconsistent, and member motivation weakened. The study underscores the need for intentional team-building, empathetic leadership communication, and ongoing conflict management in student organizations. It provides practical insights for strengthening interpersonal communication and enhancing organizational performance within Medkom and comparable student-based divisions.